Revisiting Myosin Families through Large-scale Sequence Searches Leads to the Discovery of New Myosins. (January 2016) - Pasha, Shaik Naseer; Meenakshi, Iyer; Sowdhamini, Ramanathan
Myosins are actin-based motor proteins involved in many cellular movements. It is interesting to study the evolutionary patterns and the functional attributes of various types of myosins. Computational search algorithms were performed to identify putative myosin members by phylogenetic analysis, sequence motifs, and coexisting domains. This study is aimed at understanding the distribution and the likely biological functions of myosins encoded in various taxa and available eukaryotic genomes. We report here a phylogenetic analysis of around 4, 064 myosin motor domains, built entirely from complete or near-complete myosin repertoires incorporating many unclassified, uncharacterized sequences and new myosin classes, with emphasis on myosins from Fungi, Haptophyta, and other Stramenopiles, Alveolates, and Rhizaria (SAR). The identification of large classes of myosins in Oomycetes, Cellular slime molds, Choanoflagellates, Pelagophytes, Eustigmatophyceae, Fonticula, Eucoccidiorida, and Apicomplexans with novel myosin motif variants that are conserved and thus presumably functional extends our knowledge of this important family of motor proteins. This work provides insights into the distribution and probable function of myosins including newly identified myosin classes.